Otapirian (Rhaetian) Terebratulida (Brachiopoda) of Zealandia - Macfarlan, Donald Alexander Bankier (Zootaxa, 2023)
Terebratulides are present throughout the Zealandian Rhaetian (Otapirian local stage), but only Zeilleria spiculata has been described to date. Others have been recorded, mainly as Dielasma. A total of seven species are recorded here. In this paper, two new species are included in the dielasmatid genus Tibetothyris Jin and Sun, 1976. Tibetothyris hamishi n. sp. is found in New Caledonia and the Kawhia and Southland synclines. Tibetothyris johnstoni n. sp. is found in New Caledonia, Nelson, and the Taringatura Hills in western Southland. A large, biconvex terebratulide that is common at a few localities in île Ducos and île Hugon, New Caledonia, in Nelson, and probably in Southland, belongs to the cosmopolitan genus Rhaetina and is described as Rhaetina rainei n. sp. Lobothyris richardsi n. sp. is proposed for a Lobothyris with a distinctive straight anterior margin. This has some resemblance to the Siberian and North American Late Triassic species Lobothyris monstrifera Dagys, 1963. As well as Z. spiculata, two other species of Zeilleria are recognized from the Otapirian of Zealandia. A small form that has some similarity to the Early Jurassic Zeilleria terezowae is here named Z. minima n. sp. A single specimen of a larger, strongly inflated species is described as Zeilleria n. sp. The fauna as a whole is cosmopolitan, with affinities to the Circumpacific region.